2013
DOI: 10.1182/blood-2012-04-425033
|View full text |Cite
|
Sign up to set email alerts
|

Potent obatoclax cytotoxicity and activation of triple death mode killing across infant acute lymphoblastic leukemia

Abstract: Key Points Infant acute lymphoblastic leukemia is sensitive to therapeutic targeting by apoptosis, necoptosis, and autophagy activation whether MLL is rearranged or germline. The disease-specific form of triple death mode killing by obatoclax overcomes the intrinsic resistance of MLL-rearranged infant acute lymphoblastic to cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 40 publications
3
53
0
Order By: Relevance
“…ABT-263 was modestly effective in reducing cell viability, while Obatoclax efficiently inhibited cell proliferation in all the three Kras G12D , p53 −/− cell lines tested (Figure 6A), with IC 50 ’s in the low nanomolar range. While at lower doses Obatoclax induced, as previously shown in other cells (Urtishak, et al 2013), an accumulation of cells in S-phase without evidence of cell death (Figure 6B, C), treatment with 500nM Obatoclax for 48 hours induced massive cell death (Figure 6C). Thus, Kras G12D , p53 −/− cells are effectively killed by BH3 mimetics that specifically bind to and inhibit Bcl2a1 and Mcl1.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…ABT-263 was modestly effective in reducing cell viability, while Obatoclax efficiently inhibited cell proliferation in all the three Kras G12D , p53 −/− cell lines tested (Figure 6A), with IC 50 ’s in the low nanomolar range. While at lower doses Obatoclax induced, as previously shown in other cells (Urtishak, et al 2013), an accumulation of cells in S-phase without evidence of cell death (Figure 6B, C), treatment with 500nM Obatoclax for 48 hours induced massive cell death (Figure 6C). Thus, Kras G12D , p53 −/− cells are effectively killed by BH3 mimetics that specifically bind to and inhibit Bcl2a1 and Mcl1.…”
Section: Resultssupporting
confidence: 84%
“…Thus, targeted inhibition of anti-apoptotic proteins appears to be a valid strategy to sensitize otherwise resistant thyroid cancer cells to cell death induced by inhibition of the driver pathway or cytotoxic chemotherapy. In view of the possible ability of Obatoclax to induce different modes of cell death, including apoptosis, necroptosis, and autophagic death (Basit, et al 2013; Heidari, et al 2010; Urtishak et al 2013; Yu and Liu 2013), future studies are needed to dissect in depth the specific route through which RAS mutant thyroid cells undergo cell death upon inhibition of anti-apoptotic Bcl2 family members, so that additional fine tuning of the death-inducing system can be achieved for optimal therapeutic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies using different cell lines have suggested that Obatoclax may induce necroptosis, a regulated form of necrosis that depends on RIP1 kinase activity [25, 26]. However, a RIP1 inhibitor, necrostatin-1, was completely unable to prevent Obatoclax-induced necrosis in thyroid cancer cells (Figure 1H).…”
Section: Resultsmentioning
confidence: 81%
“…It was developed from a compound identified in a natural compound library that disrupted interactions between BCL-2 family proteins [46]. Preclinical studies with obatoclax demonstrated that it inhibited the growth of cells lines and primary samples in several models such as myeloma, systemic mastocytosis, mast cell leukemia, acute lymphoblastic leukemia and acute myeloid leukemia [4751]. Obatoclax-induced apoptosis was associated with release of cytochrome c and activation of the BAX/BAK complex [49].…”
Section: Targeting the Apoptosis Pathwaymentioning
confidence: 99%
“…Combination studies with obatoclax have been more successful both in in vitro and in vivo models. Obatoclax has been shown to synergize with chemotherapy, NVP-BE2235 (PI3K inhibitor), PKC412 (KIT inhibitor), dexamethasone, to name a few [47,48,50,51,55]. …”
Section: Targeting the Apoptosis Pathwaymentioning
confidence: 99%